The smoking-dyslipidaemia dyad: A potent synergistic risk for atherosclerotic coronary artery disease. (March 2021) - Prakash, Vineet; Jaker, Sams; Burgan, Amjad; Jacques, Adam; Fluck, David; Sharma, Pankaj; Fry, Christopher H; Han, Thang S
Background: Smoking and dyslipidaemia are known individual risk factors of coronary artery disease (CAD). The present study examined the combined risk of smoking and dyslipidaemia on coronary atherosclerosis. Methods: Coronary artery calcium (CAC), measured by cardiac CT, was used to assess the extent of CAD, which was related to smoking and dyslipidaemia using logistic regression, adjusted for age, sex, hypertension, BMI and family history of ischaemic heart disease. Results: Seventy-one patients (46 men, 25 women: median age of 53.7yrs; IQR = 47.0–59.5) were recruited. The mean log10 CAC score in never-smokers without dyslipidaemia (reference group) was 0.37 (SD = 0.73), while the value in those with a history of smoking was 0.44 ± 0.48 (mean difference: 0.07, 95%CI:–0.67 to 0.81, p = 0.844), dyslipidaemia was 1.07 ± 1.08 (mean difference: 0.71, 95%CI: 0.24 to 1.17, p = 0.003), and both risk factors was 1.82 ± 0.64 (mean difference: 1.45, 95%CI:0.88 to 2.02, p < 0.001). For individuals in the reference group, the proportions with none, one and multiple vessel disease were 80.6%, 16.1% and 3.2%; for those with a history of smoking or with dyslipidaemia were 50.0%, 25.0% and 25.0%; and for those with both risk factors were 8.3%, 25.0% and 66.7%. Patients with a history of both risk factors had greater adjusted risks of having one- vessel disease - OR = 14.3 (95%CI = 2.1–98.2) or multiple vessel disease: OR = 51.8 (95%CI = 4.2–609.6). Conclusions: Smoking and dyslipidaemia together are associated with high coronary artery calcification and CAD, independent of other major risk factors.